2000
DOI: 10.1111/j.1472-8206.2000.tb00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the endothelium on the response to adrenoceptor agonists of rabbit aorta during cooling

Abstract: The role of the endothelium in the effects of cooling on the response to alpha1- and alpha2-adrenoceptor agonists of rabbit aorta was studied. The contractions induced by clonidine (10(-9)-3 x 10(-4) M) and xylazine (10(-7)-10(-3) M) but not phenylephrine (10(-9)-3 x 10(-4) M) and methoxamine (10(-9)-3 x 10(-4) M) were enhanced in endothelium-denuded or N(G)-nitro-L arginine methyl- ester (L-NAME) (10(-5) M) pretreated rabbit aorta. The sensitivity, but not the maximal response, of both alpha1- and alpha2-adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
3
11
0
2
Order By: Relevance
“…In the present study, we also investigated the role of nitric oxide in cooling-and warming-induced responses. In previous studies, we observed similar findings in different tissues such as rabbit aorta [14], calf coronary artery and cardiac vein [15,16]. This suggested that during cooling or warming the response to the vasoconstrictors is not modulated by nitric oxide.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, we also investigated the role of nitric oxide in cooling-and warming-induced responses. In previous studies, we observed similar findings in different tissues such as rabbit aorta [14], calf coronary artery and cardiac vein [15,16]. This suggested that during cooling or warming the response to the vasoconstrictors is not modulated by nitric oxide.…”
Section: Discussionsupporting
confidence: 82%
“…The temperatures utilized in this study; 28°C, for cooling was considered to be 'moderate cooling' temperature accordingly to our previous studies [14,15] and 41°C for warming was chosen to include body temperature experienced during passive or exertional warming under physiological or pathophysiological conditions. Furthermore, data from in vitro preparations warmed to 40°C or higher are equivocal [12,25].…”
Section: Discussionmentioning
confidence: 99%
“…The ice-water test is a simple supplementary urodynamic test that increases the precision of the diagnosis of infant detrusor overactivity (Geirsson et al, 1999). The temperature utilized in this study; 28ºC, for cooling was considered to be "moderate cooling" temperature accordingly to our previous studies (Atalık et al, 2000;Atalık et al, 2001;Atalık et al, 2008). In our study, compared with the control responses at 37ºC, cooling increased both the sensitivity and the maximum responses to ACh and KCl in both non-diabetic and STZ-induced diabetic urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in diabetic animals, contractile responses of the urinary bladder to muscarinic agonists are inconsistent. Some investigators have reported increased responses (Tong et al, 2002;Nsabimana and Ojewole, 2008), while others have reported decreased responses (Licoln et al, 1984;Longhurst et al, 1986), or no change in contractile responses (Luheshi and Zar, 1991;Atalık et al, 2000) of diabetic urinary bladder smooth muscle strip to muscarinic agonists.…”
Section: Introductionmentioning
confidence: 99%
“…The calf cardiac vein is easily accessible smooth muscle preparations and there is a limited information (13-16) about the effects of temperature in these vessels and the effects of cooling were generally studied with contractile agents. Furthermore, to our The temperature utilized in this study; 28 °C, for cooling was considered to be 'moderate cooling' temperature accordingly to our previous studies (13,17).…”
Section: Discussionmentioning
confidence: 99%